77.3k views
4 votes
Solve the equation: 3x - x + 2 = 4(2x - 1) infinite solutions x = 1 x = -1 no solution

2 Answers

5 votes
X = 1

Porque:

3x - x + 2 = 4(2x - 1)

3x - x + 2 = 8x - 4

3x - x - 8x = - 4 - 2

- 6x = - 6

x = - 6/ -6

x = 1 ✔️


User Xeranic
by
5.2k points
4 votes

Answer:


x=1

B

Explanation:

So we have the equation:


3x-x+2=4(2x-1)

Combine like terms on the left:


3x-x+2=4(2x-1)\\2x+2=4(2x-1)

Distribute out the right:


2x+2=4(2x-1)\\2x+2=8x-4

Subtract 2x from both sides. The left side cancels:


(2x+2)-2x=(8x-4)-2x\\2=6x-4

Add 4 to both sides. The right side cancels:


2+4=(6x-4)+4\\6=6x

Divide each side by 6:


(6)/6=(6x)/6\\x=1

Therefore, the solution is: x=1.

User Mansfield
by
4.7k points